2021
DOI: 10.1186/s13075-020-02405-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarker panel for the diagnosis of rheumatoid arthritis

Abstract: Background Rheumatoid arthritis (RA) is an autoimmune disease of inflammatory joint damage, wherein C-reactive protein and autoantibodies including rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) are rapidly elevated. These serological factors are diagnostic markers of RA; however, their sensitivity and specificity for prediction warrant improvement for an early and accurate diagnosis. Methods We aimed to identify alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
2
24
0
2
Order By: Relevance
“…An experimental study used label-free quantitative proteomics to characterize proteins with diagnostic potential, especially for seronegative RA patients. It has been demonstrated that serum amyloid A-4 protein (SAA4), retinol-binding protein-4 (RBP4), angiotensinogen (AGT) and vitamin D-binding protein (VDBP) are accurate enough to be used as diagnostic tools [ 115 ]. Glycoprotein YKL-40 can be used as a diagnostic biomarker because of its promising results [ 116 ].…”
Section: Clinical Aspects Of Ramentioning
confidence: 99%
“…An experimental study used label-free quantitative proteomics to characterize proteins with diagnostic potential, especially for seronegative RA patients. It has been demonstrated that serum amyloid A-4 protein (SAA4), retinol-binding protein-4 (RBP4), angiotensinogen (AGT) and vitamin D-binding protein (VDBP) are accurate enough to be used as diagnostic tools [ 115 ]. Glycoprotein YKL-40 can be used as a diagnostic biomarker because of its promising results [ 116 ].…”
Section: Clinical Aspects Of Ramentioning
confidence: 99%
“…Prior research has shown that rheumatoid factor serves as an important index of diagnosis for rheumatoid diseases, with sensitivity and specificity being 60–90% and 85%, respectively. This finding indicates that the diagnosis of some patients with joint pain might not be accurate, especially at the early stages ( Mun et al, 2021 ). Our in-depth review of OA cases found the proportion of such patients was still on the increase ( Mobasheri, 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…Several proteins and peptides have been identified that are unique to serum proteome of RA patients [ 18 , 20 ]. A recent study compared the serum proteome profiles of seronegative patients with healthy controls [ 21 ]. However, to our knowledge, no study has compared the serum proteome profiles of all the RA serotypes based on ACPAs and RF.…”
Section: Introductionmentioning
confidence: 99%